Diagnóstico y evaluación del clima laboral en el departamento contable de la empresa Baker Hughes de la ciudad de Quito - Rhon Martin, María Elena (2013)
This work there presents a diagnosis and evaluation of the labour climate of the Countable Department of Baker Hughes Company in Quito city, with the intention of supporting this organization to identifying the fortresses and areas of opportunity that could be identified from this investigation, which will be achieved by the support and collaboration of the members of this department.